Peran Pendidikan Dalam Membangun Kesadaran Hukum Di Masyarakat - Pasya Islami Geni Putra; Azlan Aris; Gusmaneli (CV. ITTC INDONESIA, 2024)
Education has a crucial role in building legal awareness in society through introducing legal concepts from an early age. By integrating legal material in the curriculum, students can understand their rights and obligations as well as the values ​​that underlie the law. Effective legal education can reduce legal violations and encourage law-abiding attitudes and social ethics. Apart from that, education also functions as a means of preventing legal violations by providing an understanding of the legal consequences. Through interactive learning methods, students can develop critical thinking skills and be responsible for the law. Collaboration between schools, parents and the community is very important to create an environment that supports legal awareness. With a comprehensive approach, it is hoped that future generations will better appreciate and apply the law in their daily lives, thereby contributing to the creation of a more just and civilized society.